1998
DOI: 10.1310/gywa-96br-4laj-9k18
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Community Reintegration, Coping Strategies, and Life Satisfaction in a Sample of Persons with Spinal Cord Injury

Abstract: IFE satisfaction is one of the components of subjective quality of life described by Diener, 1 and because tive quality of life as an important outcome of rehabilitation, [2][3][4][5] the study of life satisfaction is a timely endeavor. In a recent article combining scholarship and passion, deLateur 6In this study of 78 people living in the community 1 to 7 years after spinal cord injury, community integration and reported coping strategies were investigated for their association with life satisfaction. Commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…In total, 18 of the 77 associations between active problem-focused coping variables and QOL were significant. 21,[29][30][31]33,34,36,37,[42][43][44]58,59 All active problem-focused coping variables showed more nonsignificant than significant relationships, and did not show consistent relationships with QOL outcome measures over time.…”
Section: Appraisalsmentioning
confidence: 89%
See 2 more Smart Citations
“…In total, 18 of the 77 associations between active problem-focused coping variables and QOL were significant. 21,[29][30][31]33,34,36,37,[42][43][44]58,59 All active problem-focused coping variables showed more nonsignificant than significant relationships, and did not show consistent relationships with QOL outcome measures over time.…”
Section: Appraisalsmentioning
confidence: 89%
“…In all, 7 of 13 associations between blaming oneself for one's SCI and QOL were significant. 15,[23][24][25][26][27][28][29][30] Self-blame was associated weakly with higher life satisfaction, 15 lower posttraumatic stress 25 and lower psychological distress. 23 Inconsistently, self-blame was also correlated with greater depression in one study, 26 and with less depression in two other studies.…”
Section: Psychological Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…20,21 Relationship among pain variables and community reintegration Our results suggest pain impact and pain intensity are both key factors that relate to one's ability to reintegrate to the community, with pain intensity accounting for 25% of the variability, while the addition of the FIM and pain impact accounted for a total of 37% of the variance in RNL scores. This is a worthy finding given that a myriad of factors can potentially influence one's adjustment to the community, including motivation, education, family support, ethnicity and the availability of appropriate resources.…”
Section: Discussionmentioning
confidence: 83%
“…This is a worthy finding given that a myriad of factors can potentially influence one's adjustment to the community, including motivation, education, family support, ethnicity and the availability of appropriate resources. 20,21 One study that has examined pain and community reintegration reported that individuals with long term SCI (mean length of injury ¼ approx. 7.4 years) who had extreme pain interference reported lower scores on the CHART mobility, social integration, economic selfsufficiency subscales compared to individuals who reported no pain interference.…”
Section: Discussionmentioning
confidence: 99%